KOMUNIKASI PEMASARAN TERPADU PT MUSTIKA RATU Tbk. (Studi Deskriptif Sponsorship pada Event Puteri Indonesia sebagai Usaha untuk Membangun Brand Image dan Meningkatkan Brand Awareness Mustika Ratu Oleh PT Mustika Ratu Tbk.) - , ROBY RAHMAWAN PN, Muhamad Sulhan, S.I.P, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public relations has not been seen as an integral part of marketing communicatioin many companies. Many of them only focus in mass media advertising as their promotional activity. Whereas, public relations through its communication tools, such as sponsorship can be used to reach wide audience and create awareness, as well as create the brand image. The aim of this research was to gain a deeper understanding of how PT Mustika Ratu Tbk. uses sponsorship in Puteri Indonesia to create the image and increase its awareness to build strong brand equity of Mustika Ratu. In order to achieve this purpose, the research used the descriptive-qualitative approch to describe and explain how the image and awareness were created through the event sponsorship. The theory of this research was collected from various sponsorship, brand and IMC literatures that included books, journal, and additional PT Mustika Ratu Tbkâs confidential informations and documents. The emperical study was conducted with the interviews with Corporate Public Relations Manager of PT Mustika Ratu Tbk. and Public Relations of Puteri Indonesia Organization. The findings showed that Mustika Ratu is willing to sponsor the event because it can create the image and awareness as expected, as well as can be an atribute that associated to the corporate and product brand. Sponsorship in Puteri Indonesia has been the core of PT Mustika Ratu Tbkâs integrated marketing communication strategy. To reach the best result of IMC objectives, the winner of Puteri Indonesia will be used in other marketing communication tools such as advertising, promotion, and CSR activities as brand personafication of Mustika Ratu.